A Global Review on Locusts (Orthoptera: Acrididae) and Their Interactions With Livestock Grazing Practices - Le Gall, Marion; Overson, Rick; Cease, Arianne (Frontiers in Ecology and Evolution, 2019)
Connections between locusts and people date back millennia and locusts remain a major food security challenge today throughout the world. Locust biology is often linked to abiotic conditions like temperature and/or precipitation, fueling the perception that aside from active control, humans are not a key player in the interaction locusts have with their environment. However, several studies have shown that land management practices like grazing heavily influences locust-human linkages. In this review we synthesize published research and reports on connections between locust outbreaks and ranching. For this, we conducted an extensive literature search using Google Scholar on the 19 species of grasshoppers that are currently considered to be locusts or non-model locusts. Species were sorted according to their feeding guilds: 1) forb- and/or tree-feeding locusts; 2) mix-feeding locusts (grasses, forbs, and/or trees); 3) grass-feeding locusts. We reviewed their pest status, ecology, and relationship with grazing. We then discussed the overall data and draw general patterns on how locusts and locust control affect livestock grazing through various mechanisms (competition, nutritional preferences, pesticide use, nutrient cycling). We draw attention to “telecoupling” a process in which land management practices like grazing have ecological feedbacks on locust populations, which in turn affects food security in distant regions due to the migratory capacity of locusts. Finally, we present new perspectives for sustainable management practices that integrate understanding of land management.